ZAKAT AS AN ALTERNATIVE ISLAMIC FISCAL POLICY IN INDONESIA - Dina Arfianti Siregar; Shabri Abd. Majid; Ridwan Ridwan (SEAN Institute, 2023)
Zakat is one of the pillars of Islam. The difference is that zakat is not only part of the routine of worship, but also has a strong relationship with social life which is directly related to socio-economic activities. This study aims to introduce zakat as an alternative to Islamic fiscal policy in Indonesia, the method is carried out using descriptive descriptive research using primary and secondary data that reveals phenomena and facts related to the management of zakat as an instrument of Islamic fiscal policy. From this study the authors get the result that from several studies conducted, many have discussed zakat as an alternative to Islamic fiscal policy, therefore zakat has a great opportunity as a source of state revenue by following the provisions of existing zakat rules or regulations.